1981
DOI: 10.1128/aac.19.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of lower respiratory tract infections with moxalactam

Abstract: Moxalactam was evaluated in the therapy of lower respiratory tract infections in 40 patients. The most common organisms isolated were Streptococcus pneumoniae (37.2%) and Haemophilus influenzae (21.5%). Gram-negative enteric organisms were isolated from six patients. No The majority of patients were febrile >38.4°C and had an accompanying leukocytosis. All patients had the following laboratory tests before, during, and upon completion of therapy: alkaline phosphatase, serum glutamic oxalacetic transaminase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…One of our failures had an organism with borderline susceptibility (MIC, 32 ,ug/ml; disk, 20 mm) and deteriorated after initially responding to moxalactam treatment. Our experience with pleuropulmonary infections was less favorable than that of other investigators (11); this was perhaps due to patients with "complicated" pleuropulmonary infections who required long courses of therapy and had a propensity to develop resistant organisms.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…One of our failures had an organism with borderline susceptibility (MIC, 32 ,ug/ml; disk, 20 mm) and deteriorated after initially responding to moxalactam treatment. Our experience with pleuropulmonary infections was less favorable than that of other investigators (11); this was perhaps due to patients with "complicated" pleuropulmonary infections who required long courses of therapy and had a propensity to develop resistant organisms.…”
Section: Resultsmentioning
confidence: 41%
“…The use of moxalactam (LY-127935) in the treatment of a wide spectrum of bacterial infections has been described previously (8,11,12,19,21). However, specific data on susceptibility tests, serum levels, and cultures for anaerobes have been lacking from some of these studies.…”
mentioning
confidence: 99%
“…Moxalactam as a single agent was effective in treating bacteremia in this and other studies (12,13,17). Of 22 patients, 20 (91%) were cured.…”
Section: Resultsmentioning
confidence: 80%
“…For at least 4 h after the dose, mean serum levels were more than twice the maximum MIC for susceptible bacteria (5 ,ug/ml). Previous studies with adults (5,6,10) showed that moxalactam had a relatively small incidence of serious adverse effects. In our study, five patients developed neutropenia which resolved after therapy was completed.…”
mentioning
confidence: 99%
“…Recent clinical trials (5,6,10) in adult patients have shown that a variety of acute bacterial infections are successfully treated with moxalactam. A low incidence of drug-associated adverse reactions was reported in these studies.…”
mentioning
confidence: 99%